2013
DOI: 10.1111/inr.12022
|View full text |Cite
|
Sign up to set email alerts
|

Support needs of caregivers: case studies in South Africa

Abstract: The study findings have implications for practice and policy. Regular training and support should be offered to caregivers in order to broaden their understanding of learning disabilities and enhance their caring ability. Nurses are the main source of training and support and offer these during clinic-based engagement and home visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 14 publications
(25 reference statements)
2
40
0
Order By: Relevance
“…Our study further indicates a lack of access to information about cerebral palsy among caregivers. This is comparable to what has been described in several other studies in low‐resource settings including studies in South Africa and Cambodia (Morgan & Tan, ; Sandy, Kgole, & Mavundla, ) and suggests that standardized educational materials or educational interventions could be helpful for families.…”
Section: Discussionsupporting
confidence: 89%
“…Our study further indicates a lack of access to information about cerebral palsy among caregivers. This is comparable to what has been described in several other studies in low‐resource settings including studies in South Africa and Cambodia (Morgan & Tan, ; Sandy, Kgole, & Mavundla, ) and suggests that standardized educational materials or educational interventions could be helpful for families.…”
Section: Discussionsupporting
confidence: 89%
“…According to Resch et al (2010), providing information to parents on the type of disability and services available at the time of diagnosis helps reduce parental stress. In a study conducted in South Africa, caregivers of children with learning disabilities reported that their lack of knowledge about their child’s condition was one of the main causes of their experiences of distress and anxiety when caring for their children (Sandy, Kgole & Mavundla 2013). Giving information during the initial diagnosis helps families to plan for their child’s future, learn of the services available and understand the long-term implications of their child’s condition (Jeglinsky, Autti-Rämö & Carlberg 2012; Palisano et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It reduces parents' so‐called health literacy. ‘Health literacy refers to an individual's achievement of a level of knowledge, personal skills and confidence to take action to improve his or her life’ (Sandy et al ., : 349).…”
Section: Disability and Carementioning
confidence: 98%
“…It is the inability to provide for the child that creates the most stress’ (: 8). Research from Kenya, Pakistan and South Africa supports the notion of stress as a result of carers' constrained ability to satisfy their child's basic needs (respectively Gona et al ., ; Qayyum, Lasi & Rafique, ; Sandy, Kgole & Mavundla, ).…”
Section: Disability and Carementioning
confidence: 99%